Kernel distribution density estimation based on cross-validation - Kavaliauskas, Mindaugas (Lietuvos matematikos rinkinys, 2000)
The kernel density estimation procedure is proposed. Parameter selection method based on cross-validation technique is analyzed. The results of investigation by simulation means are discussed.